Experiências de educação em tempo integral no Brasil e no município de Francisco Beltrão-Pr: qual formação integral? - Ficanha, Kathiane (2015)
This reasearch aims to discuss the comprehension of integral formation presents in education proposal of full time in Brazil, on tha basis that as more time passes at school, institution whose essencial social function is to teach the foundations of knowledge historically produced and accumulated by humanity, more easily can create conditions for an emancipatory education. Provided the importance that the full-time education achieved in education for popular classes, we verified the necessity to understant it better, in an attempt to overcome the limits of assistentialism towards unilateral trainings. For that, we developed this search by which we intend to analyze the history of full-time education in Brazil, delimiting the discussion of the necessity in expansion of school time according to a given education model for working class children, for, from the whole, understand the particularity of this type of education located in the municipal school system of Francisco Beltrão since 1994, in relation to expansion of school time for an integral formation of students who stay longer at school, observing their limits and possibilities. Then comes the necessity of studies with a methodological theoretical foundation that propitiates the basement about a full-time education that focuses the formation of autonomous and active socially subjects, able to think and analyze historical, political and social knowledge under the light of a critical theory, articulated to the capitalist social context, considering the close relation among education and society. In this way, it is necessary to analyze the society as a historical whole and socially constructed and then we understand the specific reality in which includes the scholl full-time.So, we search a historical reference based on historical materialism dialectical, in an attempt to get to the synthesis about histoy of full-time education in Brazil, its influence in the city of Francisco Beltrão and the possibilities of overcoming the liberal perspective. In that perspective, we organized our research in three chapters, in which we search achieve the specific aims of this research, whether they are: 1) to know the history of education implementation in full time in our country, in relation to the way of organization of the extended time and the held formation for children in four great experiences (Escola-Parque, CIEPs, PROFIC and Programa Mais Educação); 2) the influence of that history in experiences of extension of educational time in Francisco Beltrão and the ways in which they relate the possibilities of full training of the students; 3) Understand how could emancipatory formation from full-time education based on Marxist perspective of omnilateral training and having work as an educational principle. Finally, we analyzed the necessity of surpassing the liberal model, taking full-time education as na important tool in the formation of popular classes.